BILANGAN KROMATIK UNTUK GRAF FUZZY LENGKAP DAN GRAF FUZZY BIPARTISI LENGKAP - R, Isnaini (MATEMATIKA, 2009)
A fuzzy graph G(V,σ,μ) is a graph which consist of a set of fuzzy nodes σ : V ® [0,1] and a set of fuzzy edges µ: E® [0,1], so that μ(uv) ≤ σ (u) Ùσ (v)